Implementation of Eco-Efficiency Measurement for the Agro-Tourism in Thailand - CHARMONDUSIT, Kitikorn; VARDHANABINDU, Poonperm (Journal of Environmental Management and Tourism, 2017)
Agro-tourism is an alternative type of tourism utilizing agricultural sites and activities. The amount of agro-tourism investment in Thailand has been increasing each year in line with the concerns of tourists regarding agriculture and the environment. In order to enhance the ability of agro-tourism to be both profitable and environmental-friendly, an eco-efficiency measurement was conducted. Farm Chokchai, considered as an agro-tourism site, was selected as the focus of this case study of the eco-efficiency measurement. Indicators for the measurement included environmental influences which were energy, material, water, solid waste, and greenhouse gas emission. Economic values, including net sales and numbers of tourists, were set for the calculations. Activities were specifically allocated for the effectiveness of the measurement. The outcome of the study could be useful for the practice of agro-tourism by service providers and other types of tourism service providers who wish to operate in a correct manner with regards to eco-tourism, and may enhance the capability of reaching the goal of sustainable tourism.